Trust management V 5th IFIP WG 11.11 International Conference, IFIPTM 2011, Copenhagen, Denmark, June 29 - July 1, 2011. Proceedings - Wakeman, Ian (IFIP advances in information and communication technology, 2011)
This book constitutes the refereed proceedings of the 5th IFIP WG 11.11 International Conference, IFIPTM 2011, held in Copenhagen, Denmark, in June/July 2011. The 14 revised full papers and 8 short papers presented together with the abstracts of 4 keynote talks were carefully reviewed and selected from 42 submissions. The papers feature both theoretical research and real-world case studies from academia, business and government focusing on areas such as: trust models, social and behavioral aspects of trust, trust in networks, mobile systems and cloud computation, privacy, reputation systems, and identity management.